Novel β-carbolines against colorectal cancer cell growth via inhibition of Wnt/β-catenin signaling - Li, X (Cell Death Discov, 2015)
Wnt signaling pathway is aberrantly activated in a variety of cancers, especially in colorectal cancer (CRC), because of mutations in the genes encoding adenomatous polyposis coli (APC), β-catenin and Axin. Small-molecule antagonists of Wnt/β-catenin signaling are attractive candidates for developing effective therapeutics for CRC. In this study, we have identified a novel Wnt signaling inhibitor, isopropyl 9-ethyl-1- (naphthalen-1-yl)-9H-pyrido[3,4-b]indole-3- carboxylate (Z86). Z86 inhibited Wnt reporter activities and the expression of endogenous Wnt signaling target genes in mammalian cells and antagonized the second axis formation of Xenopus embryos induced by Wnt8. We showed that Z86 treatment inhibits GSK3β (Ser9) phosphorylation, leading to its overactivation and promoting the phosphorylation and degradation of β-catenin. In vitro, Z86 selectively inhibited the growth of CRC cells with constitutive Wnt signaling and caused obvious G1-phase arrest of the cell cycle. Notably, in a nude mouse model, Z86 inhibited dramatically the xenografted tumor growth of CRC. Daily intraperitoneal injection of Z86 at 5 mg/kg resulted in >70% reduction in the tumor weight of HCT116 cell origin that was associated with decreased GSK3β (Ser9) phosphorylation and increased β-catenin phosphorylation. Taken together, our findings provide a novel promising chemotype for CRC therapeutics development targeting the canonical Wnt signaling.